Femtosecond-Laser Direct Writing of Double-Line and Tubular Depressed-Cladding Waveguides in Ultra-Low-Expansion Glass - Wu, Yuhao; Guo, Sixuan; Cheng, Guanghua; Wang, Feiran; Wang, Xu; Zhang, Yunjie (Photonics, 2025)
Addressing the stability requirements of photonic integrated devices operating over wide temperature ranges, this work achieves controlled fabrication of femtosecond-laser direct-written Type II double-line waveguides and Type III depressed-cladding tubular waveguides within ultra-low-expansion LAS glass-ceramics. The light-guiding mechanisms were elucidated through finite element modeling. The influences of laser writing parameters and waveguide geometric structures on guiding performance were systematically investigated. Experimental results demonstrate that the double-line waveguides exhibit optimal single-mode guiding performance at 30 μm spacing and 120 mW writing power. For the tubular depressed-cladding waveguides, both single-mode and multi-mode fields are attainable across a broad processing parameter window. Large-mode-area characteristics manifested in the 50 μm core waveguide, exhibiting an edge-shifted intensity profile for higher-order modes that generated a hollow beam, enabling applications in atom guidance and particle trapping.